(untitled) (Herald of Journalism, 2020)
According to the multiple researches the Internet become one of the most important tools to find all information. The youth and all adults find all information in Internet and social networks every day, while forgetting about the traditional sources for information. Saving and development of national heritage, traditions, culture and customs of our ancestors by mod ern tools of communication – the Internet and social networks – became the most actual task of modern society. The publication covers issues of propaganda’s problems of national heritage in the Internet, as well as ways of its further saving and promotion.